A study on serum lipid and malondialdehyde levels among diabetic patients - Vivekananthan, S. C.; Kumar, M. Suresh; Nagalingam, Saranya (International Journal of Research in Medical Sciences, 2019)
Background: Elevated levels of lipid peroxide in diabetes mellitus may be due to the alteration of function of erythrocytes membrane. This inhibits the activity of superoxide dismutase enzyme leading to accumulation of superoxide radicals which cause the maximum lipid peroxidation and tissue damage in diabetes. The objectives was to study was done with the objectives of assessing the serum lipid and malondialdehyde levels among diabetic population and matched control group. Methods: This study was done among 50 NIDDM, 50 IDDM and 50 controls at Thanjavur Medical College, Tamil Nadu, India for a period of one year at the Department of Diabetology after getting the informed consent and IEC clearance. This study included all ambulatory NIDDM and IDDM patients without any complications. The following investigations like serum malondialdehyde, blood sugar, HBA1C, serum lipid profile, blood urea, serum creatinine, urine albumin and sugar were done by standardized procedures and reagents after getting the detailed history and examination. Results: Among NIDDM group 78% were between 6.4 to 8 categories whereas in IDDM group only 28% were in this 6.4 to 8 category (HBA1C). Comparison of serum MDA values among three groups were done by ANOVA with two groups separately and it was highly significant. Multiple comparison of mean difference of MDA and lipid values among all the three groups showed statistically significant results with p value at 0.05. Conclusions: Lipid profile is increased in poor glycemic controlled patients (both IDDM and NIDDM patients) and it is reflected in high serum malondialdehyde levels.